Mesomorphic Properties of Symmetric Hydrogen – Bonding Dimers Containing Chalcone Moiety - A. Al-Lami, Ali kareem (Iraqi Journal of Science, 2026)
The work involves synthesis of a new homologous series of hydrogen bondingliquid crystal dimers containing chalcone moiety. All the prepared compounds werecharacterized by spectroscopic techniques such as FT – IR, 1H-NMR, 13C-NMR aswell as elemental analysis. All the synthesized dimers exhibited nematic and smecticA phase. The mesophases behaviour and transitional temperatures were studied bypolarized microscopy and differential scanning calorimetry, and are discussed theself- assemble of H-bonding donor and acceptor complexes